2014
DOI: 10.1016/j.proeps.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Uncertainty in Shallow Rainfall-triggered Landslide Modeling at Basin Scale: A Probabilistic Approach

Abstract: This study proposes a methodology to account for the uncertainty of hydrological and mechanical parameters in coupled distributed hydrological-stability models for shallow landslide assessment. A probabilistic approach was implemented in an existing eco-hydrological and landslide model by randomizing soil cohesion, friction angle and soil retention parameters. The model estimates the probability of failure through an assumed theoretical Factor of Safety (FS) distribution, conditioned on soil moisture content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
0
25
0
2
Order By: Relevance
“…Uncertainties in hydroclimatic variables, such as precipitation, air temperature, and resulting hydrologic fluxes, are particularly pronounced in steep, high mountain regions due to lack of observations to capture complex atmospheric processes (Roe, 2005;Wayland et al, 2016). Designating landslide hazard as a probability, rather than an index, systematically accounts for uncertainty and variability in stability analysis (Hammond et al, 1992;Simoni et al, 2008;Arnone et al, 2014) and more appropriately represents complex systems (Berti et al, 2012). Recently, some promising advances have been made in process-based models accounting for data uncertainty in landslide hazard mapping (e.g., Raia et al, 2014;Arnone et al, 2016a).…”
Section: Geomorphology and Modeling Backgroundmentioning
confidence: 99%
“…Uncertainties in hydroclimatic variables, such as precipitation, air temperature, and resulting hydrologic fluxes, are particularly pronounced in steep, high mountain regions due to lack of observations to capture complex atmospheric processes (Roe, 2005;Wayland et al, 2016). Designating landslide hazard as a probability, rather than an index, systematically accounts for uncertainty and variability in stability analysis (Hammond et al, 1992;Simoni et al, 2008;Arnone et al, 2014) and more appropriately represents complex systems (Berti et al, 2012). Recently, some promising advances have been made in process-based models accounting for data uncertainty in landslide hazard mapping (e.g., Raia et al, 2014;Arnone et al, 2016a).…”
Section: Geomorphology and Modeling Backgroundmentioning
confidence: 99%
“…The slope stability model explicitly accounts for the spatial heterogeneity of factors that control shallow landslides, including mechanical and hydrological soil properties (Arnone et al, , ), local topographic characteristics, and the temporal variation of soil moisture in response to precipitation events, which controls the temporal FS dynamics at the watershed scale (Simoni et al, ; Arnone et al, ; Lepore et al, ; Formetta et al, ). Possible landslide deposition paths are estimated based on the concept of run‐out distance (Bathurst et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In landslide research, a number of attempts have been reported that explicitly address ensemble techniques as a means of overcoming limitations from purely deterministic approaches or by increasing the predictive performance of statistically based landslide susceptibility mapping (e.g., Arnone et al, 2014;Cho, 2007;Haneberg, 2004;Melchiorre and Frattini, 2012;Rubio et al, 2004). None of them, however, incorporate ensemble techniques in real-time applications.…”
Section: Benefits and Types Of Probabilistic Approachesmentioning
confidence: 99%